A missense mutation in SLC26A3 is associated with human male subfertility and impaired activation of CFTR. Issue 1 (December 2017) - Wedenoja, Satu; Khamaysi, Ahlam; Shimshilashvili, Liana; Anbtawe-Jomaa, Shireen; Elomaa, Outi; Toppari, Jorma; Höglund, Pia; Aittomäki, Kristiina; Holmberg, Christer; Hovatta, Outi; Tapanainen, Juha; Ohana, Ehud; et al.
Abstract Chloride absorption and bicarbonate excretion through exchange by the solute carrier family 26 member 3 (SLC26A3) and cystic fibrosis transmembrane conductance regulator (CFTR) are crucial for many tissues including sperm and epithelia of the male reproductive tract. HomozygousSLC26A3 mutations cause congenital chloride diarrhea with male subfertility, while homozygousCFTR mutations cause cystic fibrosis with male infertility. Some homozygous or heterozygousCFTR mutations only manifest as male infertility. Accordingly, we studied the influence ofSLC26A3 on idiopathic infertility by sequencing exons ofSLC26A3 in 283 infertile and 211 control men. A heterozygous mutation c.2062 G > C (p.Asp688His) appeared in nine (3.2%) infertile men, and additionally, in two (0.9%) control men, whose samples revealed a sperm motility defect. The p.Asp688His mutation is localized in the CFTR-interacting STAS domain of SLC26A3 and enriched in Finland, showing a significant association with male infertility in comparison with 6, 572 Finnish (P  < 0.05) and over 120, 000 global alleles (P  < 0.0001) (ExAC database). Functional studies showed that while SLC26A3 is a strong activator of CFTR-dependent anion transport, SLC26A3-p.Asp688His mutant retains normal Cl− /HCO3 − exchange activity but suppresses CFTR, despite unaffected domain binding and expression. These results suggest a novel mechanism for human male infertility─impaired anion transport by the coupled SLC26A3 and CFTR.